14.2+-25.2=3.8t+26.8

Simple and best practice solution for 14.2+-25.2=3.8t+26.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14.2+-25.2=3.8t+26.8 equation:


Simplifying
14.2 + -25.2 = 3.8t + 26.8

Combine like terms: 14.2 + -25.2 = -11
-11 = 3.8t + 26.8

Reorder the terms:
-11 = 26.8 + 3.8t

Solving
-11 = 26.8 + 3.8t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3.8t' to each side of the equation.
-11 + -3.8t = 26.8 + 3.8t + -3.8t

Combine like terms: 3.8t + -3.8t = 0.0
-11 + -3.8t = 26.8 + 0.0
-11 + -3.8t = 26.8

Add '11' to each side of the equation.
-11 + 11 + -3.8t = 26.8 + 11

Combine like terms: -11 + 11 = 0
0 + -3.8t = 26.8 + 11
-3.8t = 26.8 + 11

Combine like terms: 26.8 + 11 = 37.8
-3.8t = 37.8

Divide each side by '-3.8'.
t = -9.947368421

Simplifying
t = -9.947368421

See similar equations:

| 6x^3+24x^2=0 | | 9n-1+6n-3= | | -6x+9x-5=16 | | 2x^3+10x^2-48=0 | | 26x+15=5(13x) | | 15z^3+11z^2+2z=0 | | (2x^2-3x+7)+(3x^2+6x-19)=0 | | y^2+6y=16 | | x+7-6x= | | x-[5x-1(6-9x)]=30x-1(3x+2)-(x+3) | | 4x^2+20x+13=0 | | -5(t-3)-(t+4)=8 | | (2x^2+3x+7)+(3x^2+6x-19)=0 | | 24=x-(-22) | | 2a-6/5+2=2a | | 8(11-10m)+6=-7(m-3) | | 1+5x+x-7= | | 6+1x=8 | | 5(b+2)-8b=-26 | | 6-0x=8 | | 15=2y-3 | | 4p^2=-17p-15 | | -5(3+7a)=-8(a-1)-4a | | 6-1x=8 | | 3-3p=-6 | | 3+3m-8m-2= | | 5-2h=3 | | 4+2d=10 | | 3(5x-1)+5(3x+2)=7 | | 6-2(y-6)=4y-7 | | 4t+9=-8-13 | | 5+2t=7 |

Equations solver categories